2019
DOI: 10.3892/mmr.2019.9863
|View full text |Cite
|
Sign up to set email alerts
|

β‑elemene inhibits oxygen‑induced retinal neovascularization via promoting miR‑27a and reducing VEGF expression

Abstract: The present study aimed to investigate the significant role of β-elemene in mouse models of oxygen-induced retinopathy (OIR). C57BL/6J neonatal mice were used to establish OIR models. They were divided into four groups: Normoxia, OIR, OIR control and OIR-treated. Mice in the OIR group were exposed to 75±5% oxygen for 5 days and returned to a normal oxygen environment on postnatal day 12 (P12). The OIR treated group was intravitreally injected with 1 µl β-elemene on P12 and subsequently returned to a normal oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Another inhibitory effect of miR-27a on the TGF-β signaling pathway is mediated via direct targeting of TGF-βRI transcript (20). Also, major growth factors capable of contributing to brosis pathogenesis were found to be downregulated by miR-27a, including IGF-1 and VEGF (34,35). All of the aforementioned studies are in line with our results which strongly demonstrate the protective effect of miR-27a against brosis and hence SSc.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Another inhibitory effect of miR-27a on the TGF-β signaling pathway is mediated via direct targeting of TGF-βRI transcript (20). Also, major growth factors capable of contributing to brosis pathogenesis were found to be downregulated by miR-27a, including IGF-1 and VEGF (34,35). All of the aforementioned studies are in line with our results which strongly demonstrate the protective effect of miR-27a against brosis and hence SSc.…”
Section: Discussionsupporting
confidence: 89%
“…In this regard, Deng K, et al have shown the negative regulation of PPARγ by miR-27a, too (44). Besides, in a study conducted by Ji-Hoon Cho, et al with a systems biology approach, it was found that miR-27a along with miR-23a and miR24 is upregulated in response to TGF-β by ZEB-1 transcription factor which is a major participant in EMT (35). It could be suggested that miR-27a elevation in these instances may take place upon over-activation of the TGF-β signaling pathway as a negative feedback mechanism to attenuate its physiological consequences.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, VEGFB and VEGFC are part of two signaling pathways with major roles in tumor angiogenesis and lymphangiogenesis [75]. According to Zhang et al, VEGFB and VEGFC contain a potential miR-27a-3p binding site [76], and they were overexpressed in KGN cells.…”
Section: Discussionmentioning
confidence: 99%
“…Another inhibitory effect of miR-27a on the TGF-β signaling pathway is mediated via direct targeting of the TGF-βRI transcript 22 . Also, major growth factors capable of contributing to fibrosis pathogenesis were found to be downregulated by miR-27a, including IGF-1 and VEGF 40 , 41 . All of the aforementioned studies are in line with our results which strongly demonstrate the protective effect of miR-27a against fibrosis and hence SSc.…”
Section: Discussionmentioning
confidence: 99%